2019 International Conference on 3D Vision (3DV) 2019
DOI: 10.1109/3dv.2019.00064
|View full text |Cite
|
Sign up to set email alerts
|

Unified Underwater Structure-from-Motion

Abstract: This paper shows that accurate underwater 3D shape reconstruction is possible using a single camera, observing a target through a refractive interface. We provide unified reconstruction techniques for a variety of scenarios such as single static camera and moving refractive interface, single moving camera and static refractive interface, and single moving camera and moving refractive interface. In our basic setup, we assume that the refractive interface is planar, and simultaneously estimate the unknown transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…), numerous other parameters may vary during a single survey (type of camera, availability of its model parameters, navigation quality, illumination conditions, etc.). Prior studies based on state-of-the-art deep-sea vehicles with HD cameras demonstrated reconstructions that had an accuracy of ±1 cm or better [49][50][51].…”
Section: Resulting 3d Modelmentioning
confidence: 99%
“…), numerous other parameters may vary during a single survey (type of camera, availability of its model parameters, navigation quality, illumination conditions, etc.). Prior studies based on state-of-the-art deep-sea vehicles with HD cameras demonstrated reconstructions that had an accuracy of ±1 cm or better [49][50][51].…”
Section: Resulting 3d Modelmentioning
confidence: 99%
“…Ichimaru et al [101] proposed a technique to estimate all unknown parameters of the unified underwater SfM, such as the transformation of the camera and refraction interface and the shape of the underwater scene, using the extended beam-adjustment technique. Several types of constraints are used in optimization-based refactoring methods, depending on the capture settings, and an initialization procedure.…”
Section: Startmentioning
confidence: 99%